1996
DOI: 10.1007/bf00174550
|View full text |Cite
|
Sign up to set email alerts
|

An empirical analysis of property appraisal and mortgage redlining

Abstract: The recent literature advances a hypothesis that addresses the possibility of mortgage redlining caused by a dynamic information externality in property appraisals and mortgage lending. In particular, Lang and Nakamura (1993) hypothesize that because property appraisals depend on past transactions, appraisals in neighborhoods where transactions were infrequent tend to be less precise. The greater uncertainty about house valuation in such neighborhoods can lead mortgage lenders to impose stringent requirement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 7 publications
(2 reference statements)
5
58
0
Order By: Relevance
“…For example, using a database of 600,000 residential mortgages purchased by Fannie mae in 1993, Chinloy, Cho and megbolugbe (1997) and Cho and megbolugbe (1996) discovered that 95% of the appraised values were greater than or equal to the pending sale price. This result was perhaps less than surprising given that low appraisals result in loan rejection or renegotiation and rejected loans were not represented in this database (the truncated distribution problem).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…For example, using a database of 600,000 residential mortgages purchased by Fannie mae in 1993, Chinloy, Cho and megbolugbe (1997) and Cho and megbolugbe (1996) discovered that 95% of the appraised values were greater than or equal to the pending sale price. This result was perhaps less than surprising given that low appraisals result in loan rejection or renegotiation and rejected loans were not represented in this database (the truncated distribution problem).…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…While commercial interests are highly visible in a mortgage case scenario as both banks and real estate buyers have an interest in completing a finance transaction (Cho & Megbolugbe, 1996;Smolen & Hambleton, 1997), our review indicated mixed results on the effects of client pressure on valuation judgement upon finance transactions. Given the indispensable role of market valuation for mortgage lending activities, we consider additional research a necessity to stipulate more closely the effect of a mortgage loan scenario upon judgement bias.…”
Section: Discussion Of Resultsmentioning
confidence: 85%
“…The valuer understands the financial implications of withdrawn transactions to clients and at the same time seeks a long-term business relation. This potentially creates a moral hazard issue for valuers with regard to deciding on an appropriate market value estimate (Cho & Megbolugbe, 1996;Kinnard, Lenk, & Worzala, 1997). In turn, the principal's awareness of this moral hazard issue opens the door for client influence.…”
Section: Professional Autonomy In Real Estate Valuationmentioning
confidence: 99%
“…His finding is similar to the findings in Hong Kong (Wong, 2006). Other studies carried out to identify the existence of and nature of anchoring and adjustment in the valuation process include (Cho and Megbolugbe, 1996;Diaz, 1997;Diaz andHansz, 1997, 2001;Hamilton and Clayton, 1999;Harvard, 1999Harvard, , 2001Clayton, Geltner, and Hamilton 2001;Hansz and Diaz 2001;Gallimore and Gray 2002;Cypher and Hansz, 2003;Hansz, 2004a;2004b). These studies confirmed the existence of anchoring and adjustment heuristics except Diaz (1997).…”
Section: Introductionmentioning
confidence: 99%